How Did the Archaellum Get Its Rotation? - Ortega, Davi; Beeby, Morgan (Frontiers in Microbiology, 2022)
How changes in function evolve fascinates many evolutionary biologists. Particularly captivating is the evolution of rotation in molecular machines, as it evokes familiar machines that we have made ourselves. The archaellum, an archaeal analog of the bacterial flagellum, is one of the simplest rotary motors. It features a long helical propeller attached to a cell envelope-embedded rotary motor. Satisfyingly, the archaellum is one of many members of the large type IV filament superfamily, which includes pili, secretion systems, and adhesins, relationships that promise clues as to how the rotating archaellum evolved from a non-rotary ancestor. Nevertheless, exactly how the archaellum got its rotation remains frustratingly elusive. Here we review what is known about how the archaellum got its rotation, what clues exist, and what more is needed to address this question.